A study on the relationship between salary, supervision and reward and recognition towards job satisfaction in Kin Kee Group / Ainun Salwani Zainal Abidin - Zainal Abidin, Ainun Salwani (Faculty of Business and Management, 2009)
Job satisfaction is a general attitude towards an individual's current job and organization that encompasses the feelings, beliefs, and thoughts about that job. Job satisfaction is likely the most studied attitude in organizational behavior (Cranny, Smith, and Stone). Most people believe that job satisfaction is closely associated with performance and numerous other important work behaviors, including absenteeism, turnover, and organizational citizenship behavior. Employees' job satisfaction is both a goal in itself and a proxy for an organization's capacity to retain and motivate its employees (Fisher and Locke; Locke).